Gain-control Raman fiber amplifier incorporating ring cavity - Ahmad, Asmahanim; Md Ali, Mas Izyani; Zamzuri, Abdul Kadir; Mahdi, Mohd Adzir (IEEE, 2005)
All-optical gain-control Raman fiber amplifier (RFA) based on ring cavity technique using a pair of circulators is investigated experimentally. A pair of 1465 nm laser diodes are used as the pump source to the RFA which provides a gain peak at around 1565 nm. The analyses of gain and noise figure are carried out using lasing wavelengths of 1550 and 1565 nm. Gain and noise figure variations are 0.4 and 0.5 dB respectively. We observed strong influence of pump-signal relative intensity noise transfer that results in noise figure penalty.